SMART SUPPLY CHAIN MANAGEMENT USING AI AND MACHINE LEARNING (International Journal of Food and Nutritional Sciences, 2022)
Numerous reasons, including as trade protectionism, anti-globalization views, and the COVID-19 pandemic, have had a substantial influence on the global supply chain environment. In this regard, implementing artificial intelligence (AI) technology has become a key tactic for improving the resilience and effectiveness of supply chains. This study looks at the variables that affect businesses of Maharashtra inclination to use AI technology and looks at how this adoption might enhance the performance and resilience of supply chains. To test our theories, we surveyed 318 Maharashtra firms using the technology-organization-environment framework and the resource-based theory. Our results show that organizations' readiness for AI adoption is highly influenced by variables including supply chain collaboration, the perceived advantages of AI technology, and environmental unpredictability. Furthermore, we discover that companies that are more open to implementing AI technology have more resilient and effective supply chains. The report emphasizes how crucial it is to take these things into account when implementing AI technology and managing supply chains. For companies and politicians looking to use AI technology to improve supply chain operations in the changing global landscape, these results offer insightful information.